Penguatan Fungsi Kesehatan Yustisial melalui Pembangunan RSU Adhyaksa - Saragih , Yusnelvi (Pusat Strategi Kebijakan Penegakan Hukum, Kejaksaan Agung, 2025)
The rise in narcotics cases, overcrowding in correctional institutions, and the limited availability of judicial health services necessitate healthcare facilities that support the law enforcement process quickly, objectively, and accountably. The urgency of this paper arises from the need to strengthen the judicial health function of the Prosecutor's Office through the construction of Adhyaksa General Hospital (RSU Adhyaksa) as a facility that can provide assessment, rehabilitation, clinical forensics, and medical care to parties proven to be in conflict with the law. This study uses a policy analysis method, comparing three policy options: the status quo, collaboration with external hospitals, and the construction of a hospital managed directly by the Prosecutor's Office. The results show that the third option has the highest legal effectiveness, is strictly regulated, and has significant potential to contribute to recovery and reduce overcrowding. This study concludes that Adhyaksa General Hospital is a strategic instrument in realizing humane, transparent, and corruption-free law enforcement, in accordance with the direction of national criminal justice system reform.